The Influence Of Population, Economic Growth And Human Development Index On Income Inequality (Case Study Of Gowa District) - Mirani, Anis; Bado, Basri; Regina, Regina; Kamaruddin, Citra Ayni; Rahim, Abd. (International Journal on Social Science, Economics and Art, 2025)
This study looked at how Gowa Regency's population, economic growth, and HDI affected income inequality between 2014 and 2023. Multiple linear regression analysis is the quantitative method employed in this study. The findings show that whereas economic development has no discernible impact on income inequality, the population variable has a positive and considerable impact. On the other hand, Gowa Regency's income disparity is significantly and negatively impacted by the Human Development Index (HDI). To get more thorough and reliable results, future researchers interested in related subjects are urged to increase the sample size and include more variables.